Blinded by the night: an examination of the veil-of-darkness within traffic enforcement before and during the COVID-19 pandemic - Vito, Anthony Gennaro (Policing during the COVID-19 pandemic, 2024)
The current study examines racial profiling during the COVID-19 pandemic through the theoretical lens of the veil-of-darkness (VOD) hypothesis. In order to test the VOD hypothesis traffic stop data from New Orleans, LA, between 2018 and 2022 were utilized along with census tract data from the AQ AQ: Please define ACS.ACS for 2014–2018. VOD findings show no evidence of racial profiling in terms of the availability of daylight impacting an officer’s decision to stop AQ AQ: Can ‘black’ and ‘white’ be changed to lowercase as in some other chapters or OK as is? Please suggest.Black drivers. However, indirect measures of race, including vehicle makes most distinctly popular among one race revealed, were related to drivers’ race. Moreover, the findings showed that time of day impacted the likelihood of searches conducted during a traffic stop, which may be indicative of racial bias.